2012
DOI: 10.3109/07420528.2012.675262
|View full text |Cite
|
Sign up to set email alerts
|

Night Work and Mortality: Prospective Study Among Finnish Employees Over the Time Span 1984 to 2008

Abstract: There is considerable evidence showing that night work is associated with increased morbidity, but only a few studies have focused on its relation to mortality. This study investigates the relationship between the type of working-time arrangement (weekly night work/daytime work) and total and cause-specific mortality among men and women. The data consist of a representative working conditions survey of Finnish employees conducted in 1984 (2286 men/2216 women), which has been combined with register-based follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
2
23
1
Order By: Relevance
“…We only included studies published since 2006, as these tend to be of higher quality and also because our aim was to update the previous meta-analysis. Indeed, the studies that presented estimates for CHD and CVD mortality were published in recent years (2010-2016) and thus most of these (16,18,38) were not included by Vyas et al (7), which may explain some of the different results. Ten studies have reported on shift work and the risk of CVD since the previous meta-analysis (16, 18, 19, 27-29, 34, 38, 39, 41); these are included in our study.…”
Section: Comparison With Other Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…We only included studies published since 2006, as these tend to be of higher quality and also because our aim was to update the previous meta-analysis. Indeed, the studies that presented estimates for CHD and CVD mortality were published in recent years (2010-2016) and thus most of these (16,18,38) were not included by Vyas et al (7), which may explain some of the different results. Ten studies have reported on shift work and the risk of CVD since the previous meta-analysis (16, 18, 19, 27-29, 34, 38, 39, 41); these are included in our study.…”
Section: Comparison With Other Studiesmentioning
confidence: 91%
“…Other studies considered doing long working hours or weekend work as shift work (34,35). Two studies did not provide a definition of shift work (36,37), while others limited inclusion to fixed night shift workers (38)(39)(40), or considered shift work as any type of work schedule other than fixed day-only work (41).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Studies on the association between elevated NSW and cancer-related mortality have produced contradicting results. Similarly, several prospective cohort studies have reported NSW in relation to all-cause mortality, but the findings were inconsistent [11,15,16]. In addition, the relationship of NSW to cardiovascular events was also unclear [15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 95%
“…Recent prospective cohort studies had reported the correlation between NSW and tumor mortality [7,[11][12][13][14]. Studies on the association between elevated NSW and cancer-related mortality have produced contradicting results.…”
Section: Introductionmentioning
confidence: 96%
“…33 This internal desynchronization in part explains why long-term night-shift workers have increased incidence of cardiovascular disease, metabolic syndrome, elevated inflammatory markers, and, in women, elevated cancer risk. [34][35][36][37] Thus, it follows that circadian disruptions and related molecular changes have an important bearing on the patient's ICU experience and outcomes.…”
Section: Consequences Of Intensive Care Unit Sleep Disruptionmentioning
confidence: 99%